Líquenes como bioindicadores de calidad del aire (2018)
The present work contains the importance of the community of lichens in the environment, since they play a very important role as bio-indicators of air quality, which have been and continue to be used in studies aimed at evaluating the effects of the activity human in the quality of the air. This can be defined in a general way as the recognition and determination of environmental, natural or human-induced changes through biota. The urban growth that has been witnessed in recent years in Cali and Jamundí, and the increase in infrastructure works that this implies for good urban development, has generated an increase in the emission of pollutants into the atmosphere, however, the universities be located in this area, play an important role in the generation of pollutants, as the demand in the automotive sector has increased because of the need for a safe and comfortable mobility to these, as a result of this increased daily traffic, decrease in green areas by construction of roads and buildings, and degradation of air quality. For these reasons it is important to implement effective and economic methods to detect changes and the current status regarding air quality in these areas, and according to the type of results, both positive and negative that are thrown when implementing these methods, generate timely relevant proposals to reduce, mitigate or avoid the generation of a future environmental problem that may mean some kind of risk, given that the quality of environmental resources in general, is linked in terms of quality of life and the level of health of a community.